Understanding Esophageal Cancer: The Challenges and Opportunities for the Next Decade - Yang, Jianjun; Liu, Xiguang; Cao, Sai; Dong, Xiaoying; Rao, Shuan; Cai, Kaican (Frontiers in Oncology, 2020)
Esophageal cancer (EC) is the seventh most common cancer worldwide with over 570,000 new cases annually. In China, the incidence of EC is particularly high where approximately 90% of cases are defined as esophageal squamous cell carcinoma (ESCC). Although various risk factors have been identified, the knowledge of genetic drivers for ESCC is still limited due to high mutational loading of the cancer and a lack of appropriate EC models, resulting in limited treatment choices for EC patients. Currently, surgery, chemotherapy, radiation and limited targeted therapy options can only bring dismal survival advantages thus the prognosis for ESCC is extremely poor. However, cancer immunotherapy has unleashed a new era of cancer treatment with extraordinary therapeutic benefits, including for EC patients. This review discusses the latest understanding of the risk factors and clinical rational for EC and provides accumulated information which describes the ongoing development of immunotherapy for EC with a specific emphasis on ESCC, the most prevalent EC subtype in the Chinese population.